Competitive ability and fitness potential among the pathotypes of Puccinia triticina on wheat in India - DHARAM PAL; P. PRASAD, S.C. BHARDWAJ*, NEHA GUPTA, T.R. SHARMA, (Indian Phytopathology, 2014)
To study the competitive ability, three sets of pathotypic combinations of Puccinia triticina on wheat were inoculated on Lr13, Lr17, Lr24 and Agra local. Pathotype 77-5 (121R63-1) showed better competitive ability in comparison to other pathotypes 77(45R31), 77-2(109R31-1), 104-2(21R55) and 106(0R8) in most of the cases. Likewise in fitness studies pathotype 77-5 exhibited low incubation and latent period, high number of uredial pustules and more urediniospore production/cm2 than the other pathotypes indicating its high fitness potential. These studies elucidate the high competitive ability and fitness potential in pathotype 77-5, which explains its predominance for the last 15 years in the natural population of Puccinia triticina.